2021
DOI: 10.1007/s00262-021-03047-7
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of T cell receptor clonotypes in tumor microenvironment identifies shared cancer-type-specific signatures

Abstract: Despite the conventional view that a truly random V(D)J recombination process should generate a highly diverse immune repertoire, emerging reports suggest that there is a certain bias toward the generation of shared/public immune receptor chains. These studies were performed in viral diseases where public T cell receptors (TCR) appear to confer better protective responses. Selective pressures generating common TCR clonotypes are currently not well understood, but it is believed that they confer a growth advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Public TCRs were previously described in infectious diseases, cancer and autoimmune disease and were found to associate with clinical outcome (62)(63)(64)(65)(66)(67). Consistently with previous studies we found that public CDR3s have shorter amino acid length (68).…”
Section: Discussionmentioning
confidence: 99%
“…Public TCRs were previously described in infectious diseases, cancer and autoimmune disease and were found to associate with clinical outcome (62)(63)(64)(65)(66)(67). Consistently with previous studies we found that public CDR3s have shorter amino acid length (68).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the transcriptomic status of the cells (i.e., distribution of the cells on UMAP) within and across the clonotypes were heterogenous, suggesting that the fate of CTLs such as cell division, differentiation, survival or cell death should have been regulated by various factors including basal state of the cells, amount and frequency of the antigen stimulation or co-stimulation, cytokines etc., during T cell activation in the clinical course of disease. Recent advanced platforms are accumulating information on public TCRs in infectious diseases and cancers 60 62 . In HIV-infected patients, there are rare subjects who could control viral propagation without therapy, called HIV controllers 61 .…”
Section: Discussionmentioning
confidence: 99%